(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Purpose: To determine ocular blood flow parameters by Doppler ultrasound scanning in type 2 diabetic patients with different stages of diabetic retinopathy. Material and Methods: In this prospective study, forty-five patients (90 eyes) with type 2 diabetes mellitus were divided into three groups of 15 patients each: no diabetic retinopathy group (DR0), non-proliferative retinopathy (NPDR), and proliferative retinopathy (PDR) groups. Doppler indices such as systolic blood flow velocity (Vs), diastolic blood flow velocity (Vd), time-averaged maximum velocity (TAMXV), pulsatility index (PI) and resistivity index (RI) in the ophthalmic artery (OA), central retinal artery (CRA) and short posterior ciliary arteries (SPCA) were determined. ANOVA was used for quantitative comparisons between the three groups. Results: There was a significant (р < 0.05) decrease in (a) the Vs from 71.1 ± 20.6 cm/s in the DR0 group to 59.9 ± 16.7 cm/s in the NPDR group and 47.4 ± 16.4 cm/s in the PDR group, (b) Vd from 22.1 ± 6.9 cm/s to 17.0 ± 6.6 cm/s and 12.3 ± 5.9 cm/s, respectively; and (c) TAMXV from 37.2 ± 11.3 cm/s to 31.9 ± 9.1 cm/s and 25.3 ± 9.7 cm/s, respectively, and an increase in the RI from 0.69 ± 0.06 cm/s to 0.71 ± 0.09 cm/s and 0.75 ± 0.08 cm/s, respectively, in the OA. In addition, there was a significant decrease in the Vd from 9.9 ± 5.4 cm/s in the DR0 group to 8.1 ± 3.8 cm/s in the NPDR group and 5.5 ± 3.1 cm/s in the PDR group, and an increase in the PI from 1.34 ± 0.16 cm/s to 1.46 ± 0.28 cm/s and 1.54 ± 0.24 cm/s, respectively, and in the RI from 0.71 ± 0.06 cm/s to 0.75 ± 0.07 cm/s and 0.80 ± 0.05 cm/s, respectively, in the CRA. Moreover, there was a significant decrease in the Vd from 4.3 ± 1.6 cm/s in the DR0 group to 3.2 ± 2.0 cm/s in the NPDR group and 3.1 ± 2.2 cm/s in the PDR group, and an increase in the PI from 1.32 ± 0.21 cm/s to 1.37 ± 0.24 cm/s and 1.54 ± 0.26 cm/s, respectively, and in the RI from 0.76 ± 0.04 cm/s to 0.82 ± 0.06 cm/s and 0.82 ± 0.06 cm/s, respectively, in the SPCA. Conclusion: We found that the arteries examined in patients with diabetic retinopathy tended to have decreased blood flow velocities and increased resistivity and pulsatility indices, with the greatest changes observed in patients with PDR. In addition, the difference in mean values of most Doppler indices between the PDR and NPDR groups was larger than that between the NPDR and DR0 groups.